2014
DOI: 10.3122/jabfm.2014.02.130177
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Elective versus Emergent Hospital Admission on Patient Satisfaction

Abstract: Background: Patient satisfaction is increasingly used as a health care quality metric, although satisfaction has been associated with more intense health care, including hospitalization. Whether the increased hospitalization associated with satisfaction is limited to elective (often discretionary) hospitalization is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The findings are consistent with the hypothesis that greater use of elective hospital services is related to subsequently higher patient satisfaction (Fenton, Jerant, & Franks, 2014). To find out, where is the difference between the groups, a multivariate regression analysis for each of the group was carried out.…”
Section: Discussionsupporting
confidence: 71%
“…The findings are consistent with the hypothesis that greater use of elective hospital services is related to subsequently higher patient satisfaction (Fenton, Jerant, & Franks, 2014). To find out, where is the difference between the groups, a multivariate regression analysis for each of the group was carried out.…”
Section: Discussionsupporting
confidence: 71%
“…Overall patient experience concerning doctors, nurses, the hospital environment, the hospital experience, and discharge process is a complex construct. Previous literature has shown that higher general patient satisfaction is correlated with patient characteristics such as female gender ( 15 ), older age ( 15 ), language concordance ( 16 ), lower level of disability ( 17 ), higher degree of chronic illness ( 18 ), hospital stay attributes such as the patient being admitted electively rather than emergently ( 19 ), and incurring higher health-care expenditures ( 12 , 20 ); hospital traits themselves like being a nonteaching facility and having a smaller local population size ( 21 ); and hospitality issues like room amenities and cleanliness ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, patients admitted through the emergency department and those who required intensive care had lower satisfaction. 25,26 These types of findings have previously raised concern about the applicability of standard HCAHPS survey questions for surgical patients, as surgical hospital care may be fundamentally different from medical care. The recent development of the Surgical HCAHPS (S-CAHPS) is a step forward in assessment of patient satisfaction 27–29 and will hopefully allow further study of the factors unique to patient satisfaction in surgical patients.…”
Section: Discussionmentioning
confidence: 99%